A Simulation Model of a Three Echelon Supply Chain System with Multiple Suppliers subject to Supply and Transportation Disruptions. Issue 3 (2015) - Hishamuddin, Hawa; Sarker, Ruhul; Essam, Daryl
Abstract: A simulation study for a three stage supply chain system with multiple suppliers subject to unexpected disruptions is presented in this paper. Two types of disruptions were considered, namely supply and transportation disruption. The objective of this study is to examine the effects of disruption on the systems' total recovery costs and other performance measures. Various disruption scenarios were predefined by combining different disruption types and locations. Overall, transportation disruption with a damaged lot has more damaging effects to the whole supply chain compared to supply disruption, due to the higher lost sales quantity. In addition, back order quantity and recovery duration have a strong positive relationship to total recovery costs. The combined benefits of simulation and optimization have enabled an increased understanding of the impacts of random disruption events on the total system behaviour.